Isolation and Characterization of Cellulolytic Bacteria from Mangrove Leaf Litter in Bale Mangrove Ecosystem - Aulia, Fitri; Idrus, Agil Al; Rasmi, Ayu Citra (Jurnal Biologi Tropis, 2025)
This study aimed to isolate and characterize cellulolytic bacteria from mangrove leaf litter in the Bale Mangrove ecosystem, East Lombok. A descriptive-explorative method was employed involving serial dilution, CMC agar culture, morphological and biochemical identification, Gram staining, and qualitative cellulase activity testing using Congo red. A total of 15 bacterial isolates were obtained and analyzed. All isolates were Gram-positive, predominantly rod-shaped (bacilli), and exhibited varied colony morphologies. Biochemical tests revealed diverse metabolic capabilities, and seven isolates demonstrated cellulolytic activity, with isolate P2.2 showing the highest cellulolytic index (IS = 3.78). The findings indicate the presence of highly active cellulolytic bacteria in local mangrove litter with potential roles in natural cellulose degradation. This research confirms the ecological relevance of local microbial diversity and suggests further exploration of their enzymatic potential for biotechnology and environmental management.